Effect of Adding Thymus leptobotrys on Extra Virgin Olive Oil’s Quality and Physicochemical Parameters - Aouatif Aboudia; Manal Zefzoufi; Meriem Rafya; Naïma Zehhar; Abderraouf El Antari; Abdelaziz Abbad; Fatiha Benkhalti (Journal of Food Quality)
The present study aimed to evaluate the changes in extra virgin olive oil (EVOO) after enrichment treatments with Thymus leptobotrys, a Moroccan endemic aromatic plant. The EVOO sample was supplemented with two materials obtained from the aerial parts of T. leptobotrys: powder (2.5 and 5%) or essential oil (100 and 200 ppm). The chemical composition analysis of T. leptobotrys extracts (essential oil and powder methanolic extract) allowed the determination of its phenolic profile. Quality parameters (acidity, peroxide value, and specific extinction coefficients), color, fatty acids composition, minor components (pigments and phenol), and Rancimat oxidative stability of the control and enriched oils were measured. Rosmarinic acid and thymusin were the main identified compounds in the powder; thymusin was identified for the first time in the essential oil where it was predominant. Generally, the enrichments did not downgrade the oil from its initial category (EVOO), according to quality indexes. Adding T. leptobotrys to EVOO, especially the essential oil, enriched its phenolic profile by allowing the migration of thymusin, a lipophile flavone, without affecting its quality parameters or color.